Functional Analysis of OsMED16 and OsMED25 in Response to Biotic and Abiotic Stresses in Rice - Zhang, Huijuan; Zheng, Dewei; Yin, Longfei; Song, Fengming; Jiang, Ming (Frontiers in Plant Science, 2021)
Mediator complex is a multiprotein complex that regulates RNA polymerase II-mediated transcription. Moreover, it functions in several signaling pathways, including those involved in response to biotic and abiotic stresses. We used virus-induced gene silencing (VIGS) to study the functions of two genes, namely OsMED16 and OsMED25 in response to biotic and abiotic stresses in rice. Both genes were differentially induced by Magnaporthe grisea (M. grisea), the causative agent of blast disease, hormone treatment, and abiotic stress. We found that both BMV: OsMED16- and BMV: OsMED25-infiltrated seedlings reduced the resistance to M. grisea by regulating the accumulation of H2O2 and expression of defense-related genes. Furthermore, BMV: OsMED16-infiltrated seedlings decreased the tolerance to cold by increasing the malondialdehyde (MDA) content and reducing the expression of cold-responsive genes.